Evaluation of antioxidant and wound healing potential of pedalium murex in albino wistar rats - MOHAN.S,; DHANALAKSHMI.J,; SELVI.S, (International Journal of Pharma and Bio Sciences, 2015)
The term of medicinal plants include a various types of plants used in herbalism and some of these plants have a medicinal activities Pedalium murex is a member of the sesame family, Pedaliaceae. The present study was carried out for the characterization, physical, chemical, microbial and immunological strength of the development of new wound healing formulation for human era. The phytochemical compounds were analyzed. Twenty four male Wister albino rats (200-220 g) two months of age were used as experimental animals and were divided into four groups. In this animal model studies simple ointment of Ethanolic extract of Pedalium murex fruits at a proposition of 10% (w/w) and 20% (w/w) was applied to induced wounds in rats and compared the effects with an antiseptic agent, Povidone Iodine ointment and normal control. The model selected were excision wound model so treated animals showed a significant reduction in the period of epithelization and wound contraction. It was noticed that the Ethanolic extract of Pedalium murex fruits reduced the wound when compared with normal control. Our results support, at least in part, the uses of most plants in ethanopharmacological claims.